Analysis Of Environmental Carrying Capacity And Accompanying Capacity For Water Supply Ecosystem Services In Ternate City - Tidore, Faedly; H Tidore, Muh Faedly; Adriani, Adriani; Arif, Nurfadhilah; B, Sabaruddin (Universitas Andi Djemma Palopo, 2025)
Environmental carrying capacity and environmental load capacity (D3TLH) are important instruments in spatial planning mandated by Law No. 32 of 2009 and Law No. 26 of 2007. This study aims to analyze the environmental carrying and loading capacity based on water provisioning ecosystem services in Ternate City. Although ecosystem services-based approaches have been widely implemented across various Indonesian regions, research specifically addressing Ternate City as a volcanic island area with distinctive geographical characteristics remains considerably limited. Furthermore, water carrying capacity data for Ternate City are insufficient, and comprehensive spatial mapping illustrating the distribution of water provisioning ecosystem service potential has yet to be developed. The method used is a supply-demand comparison approach using a 1